KAJIAN ENTOMOLOGIS TERHADAP NYAMUK VEKTOR FILARIASIS LIMFATIK DI KELURAHAN SIMBANG KULON, KABUPATEN PEKALONGAN - Nurmaliza Hasan; Dwi Sarwani Sri Rejeki; Endang Ariyani Setyowati (Collaborative Medical Journal, 2025)
Lymphatic filariasis is a chronic infectious disease caused by filarial worms and transmitted to humans through the bites of various mosquito species in tropical and subtropical environments. In Indonesia, Simbang Kulon sub-district is categorized as a filariasis endemic area based on the results of finger blood surveys (SDJ), but research on entomological surveys is rare. This study aims to conduct an entomological survey (identifying and understanding the bionomics) of mosquitoes as filariasis vectors in Simbang Kulon Sub-district, Buaran District, Pekalongan Regency, Central Java Province. This study used a descriptive survey with a cross-sectional design. Mosquito capture was carried out using the Human Landing Collection and Resting Collection methods both inside and outside the house. Samples were taken to the laboratory. The results of the identification of 50 mosquitoes found 94% Culex quinquefasciatus mosquitoes and 6% Culex vishnui mosquitoes. The blood-sucking activity of Culex quinquefasciatus and Culex vishnui in the research area is eksophagic, while the resting behavior of Culex quinquefasciatus and Culex vishnui in the research area is more outdoor resting. Peak fluctuations in blood-sucking and resting activity in Culex quinquefasciatus inside and outside the house are generally at 7:00 PM - 10:00 PM. Based on the results of the research data analysis, Culex quinquefasciatus mosquitoes are a potential vector mosquito species of filariasis in Simbang Kulon Village, Pekalongan Regency